Application of blockchain technology in the human resource system - Tham, Zheng Wei (2022)
In this project, we are not looking into cryptocurrency from a financial or investment point of view but from a mathematical approach instead. The secret to which made cryptocurrency so unique and distinctive today is none other than the blockchain technology. The layman definition of a blockchain states that this particular technology acts essentially as a digital ledger of transactions which is being distributed across the entire computer system network. These transactions are being logged every minute with a secure and immutable cryptographic signature called the hash. As humanity continues to advance and evolve, the possibility of blockchain technology seemed endless. While there are numerous ideas out there anticipating on blockchain applications, this project aims to propose an investigation on correcting the current human resource system in Malaysia. Ultimately, the goal is to produce a suitable model which acts as a significant helping tool when it comes to shortlisting talents. From a traditional and standard management system to a more strategic and tactical point of view, the human resource management system in Malaysia has already improved greatly in both efficiency and quality produced. Unlike olden days, the current system suggest that managers are required to provide employees with the most appropriate and suitable on the field training before delegating them with major tasks. Instead of striving to achieve for trivial and instantaneous results, the entire recruiting process should come from a long-term prospect, considering the future growth projections and goals of the company. While this might sound ample and formidable, only the best could ever suffice society’s hunger to strive for even higher. On that account, this project focuses on implementing the blockchain technology into our current human resource management system to construct a scenario with even more fascinating and engrossing results. By merging this project’s proposed system with logistic regression analysis, a predictive model was formed to estimate individuals’ passing rate on job applications. In the meantime, this project also covered the security aspects of the proposed system by preforming a thorough investigation on security services provided together with its security mechanisms.